Pengelolaan Administrasi Surat dan Laporan Hasil Pengawasan di Inspektorat Daerah Kabupaten Pinrang - Iis. P, Meranti; Yunus, Kurniati; Amanda, Friska; Julianti (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
In summary, this study has succeeded in improving the efficiency of administrative letters and reports at the Pinrang District Inspectorate. By using an integrated electronic system, we can increase the number of incoming and outgoing letters in a more timely and accurate manner. This system digitizes letters, provides real-time status updates, and has a search feature that makes decision-making faster and more efficient. In addition, thorough training and clear work instructions have helped employees develop the skills they need to use this new system. By using this system, the Pinrang District Inspectorate can provide more timely information about community welfare, which will increase public trust in local government operations. However, the implementation of this system is not entirely free from criticism. Several characteristics, such as resistance to change, damage to technological infrastructure, and the need for more intensive training, emerged at the beginning of the implementation. This can be explained by the right steps, such as intensive socialization, long-term training, and improving the quality of internet connections in the workplace. The results of this study indicate that the implementation of the electronic system not only increases efficiency and accuracy, but also reduces operational costs, maximizes document storage space, and increases employee productivity. Therefore, this system is recommended to be adopted by other government agencies as a positive administrative modernization initiative for the public interest.